Influence of woven glass-fibre prepreg orientation on the flexural properties of a sustainable composite honeycomb sandwich panel for structural applications - Amir, Abd Latif; Ishak, Mohammad Ridzwan; Yidris, Noorfaizal; Zuhri, Mohamed Yusoff Mohd; Muhammad Asyraf, Muhammad Rizal; Syed Zakaria, Sharifah Zarina (Multidisciplinary Digital Publishing Institute, 2023)
Owing to the high potential application need in the aerospace and structural industry for honeycomb sandwich composite, the study on the flexural behaviour of sandwich composite structure has attracted attention in recent decades. The excellent bending behaviour of sandwich composite structures is based on their facesheet (FS) and core materials. This research studied the effect of woven glass-fibre prepreg orientation on the honeycomb sandwich panel. A three-point bending flexural test was done as per ASTM C393 standard by applying a 5 kN load on different orientation angles of woven glass-fibre prepreg honeycomb sandwich panel: α = 0°, 45° and 90°. The results show that most of the sandwich panel has almost the same failure mode during the three-point bending test. Additionally, the α = 0° orientation angle shows a higher maximum load prior to the first failure occurrence compared to others due to higher flexibility but lower stiffness. In addition, the woven glass-fibre prepreg orientation angle, α = 0°, has the maximum stress and flexural modulus, which directly depend upon the maximum load value obtained during the flexural test. In addition, the experimental results and analytical prediction for honeycomb sandwich deflection show good agreement. According to the result obtained, it is revealed that woven glass-fibre honeycomb sandwich panels with an α = 0° orientation is a good alternative compared to 45° and 90°, especially when better bending application is the main purpose. The final result of this research can be applied to enhance the properties of glass-fibre-reinforced polymer composite (GFRPC) cross-arm and enhance the existing cross-arm used in high transmission towers.